Integrated metagenomic and soil chemical analyses revealed shifts of microbial nutrient cycling with poplar plantation age - You, Yimin; Liu, Xiaoting; Wang, Liran; Khalid, Muhammad; Wang, Xuelai; Jiang, Luping; Wang, Fusen; Pang, Zhongyi; Peng, Yanhui; Zhao, Xiyang (Frontiers in Plant Science, 2025)
IntroductionPoplar (Populus spp.) is widely recognized as an ideal model system for studying plant-microbial interactions due to its rapid growth, genetic tractability, and ecological importance in afforestation programs. Leveraging these advantages, we investigated how poplar cultivation reshapes soil microbial communities and their nutrient cycling functions. Although plant roots are known to profoundly influence microbial community structure and functionality, comprehensive studies systematically linking poplar-induced microbiome shifts to nutrient cycling remain limited.MethodsHere, we employed an integrative approach combining metagenomic sequencing with soil nutrient analyses to assess poplar-induced changes in microbial community and metabolic activities at the root-soil interface.ResultsOur analyses revealed three major findings: (1) poplar cultivation significantly altered the composition of microbial communities—including bacteria, fungi, and archaea—and reduced the complexity of microbial interaction networks, as revealed by co-occurrence analysis; (2) poplar cultivation enhanced microbial genetic potential related to degradation pathways for starch, lignin, and aromatic compounds, as well as carbon (C) fixation, while suppressing cellulose/hemicellulose decomposition; and (3) soil nutrient cycling processes involving nitrogen (N), phosphorus (P), and sulfur (S) were reprogrammed through changes in both gene abundance (e.g., nifH, pqqC, aprA) and nutrient availability (e.g., NO3-, P). Moreover, specific microbial taxa showed strong correlations with these functional shifts, i.e., Bacteroidota correlated with P metabolism in roots/soil, Actinobacteria and Firmicutes with organic C turnover, and Gemmatimonadetes and Nitrospirae with nitrate cycling dynamics.DiscussionBy integrating poplar’s roles as both a model species and a driver of ecological change, this study elucidates how afforestation shapes soil ecosystems through complex plant-microbe-environment interactions. These findings provide critical insights for sustainable land management strategies.